Oxidative and Proteolytic Inactivation of Alpha-1 Antitrypsin in Bronchopulmonary Dysplasia Pathogenesis: A Top-Down Proteomic Bronchoalveolar Lavage Fluid Analysis - Tirone, Chiara; Iavarone, Federica; Tana, Milena; Lio, Alessandra; Aurilia, Claudia; Costa, Simonetta; Castagnola, Massimo; Messana, Irene; Vento, Giovanni (Frontiers in Pediatrics, 2021)
The study investigates the role of the oxidative and proteolytic inactivation of alpha-1 antitrypsin (AAT), in the pathogenesis of bronchopulmonary dysplasia (BPD) in premature infants. Bronchoalveolar lavage fluid (BALF) samples were collected on the third day of life from mechanically ventilated neonates with gestational age ≤ 30 weeks and analyzed without previous treatment (top-down proteomics) by reversed phase high performance liquid chromatography electrospray ionization-mass spectrometry. AAT fragments were identified by high resolution LTQ Orbitrap XL experiments and the relative abundances determined by considering the extracted ion current (XIC) peak area. Forty preterm neonates were studied: 20 (50%) did not develop BPD (no-BPD group), 17 (42.5%) developed mild or moderate new-BPD (mild + moderate BPD group) and 3 (7.5%) developed severe new-BPD (severe BPD group). Eighteen fragments of AAT and a fragment of AAT oxidized at a methionine residue were identified: significantly higher values of AAT fragments 25-57, 375-418, 397-418, 144-171 and 397-418 with oxidized methionine were found in the severe BPD group. The significantly higher levels of several AAT fragments and of the fragment 397-418 oxidized in BALF of preterm infants developing BPD, underlie the central role of an imbalance between proteases and proteases inhibitors in exacerbating lung injury and inducing most severe forms of BPD. The study has some limitations and between them the small sample size implies the need for further confirmation by larger studies.